Antibacterial bamboo joint pull rope material for tampons and preparation method of antibacterial bamboo joint pull rope material

Through the combination of modified bentonite and acrylic-acrylamide polymer, combined with chemical grafting and crosslinking reaction, the problem of re-seepage of existing tampon bamboo drawstring after water absorption is solved, and the antibacterial performance is improved, achieving better water retention and antibacterial effects.

CN119499426APending Publication Date: 2025-02-25YOULIMEI (HUBEI) TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411679778.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The bamboo drawstring of existing tampons oozes out a large amount of liquid after absorbing water, resulting in uncomfortable feeling and lacks effective antibacterial properties.

Method used

The antibacterial and water-retaining properties of the fibers are improved by chemical grafting and crosslinking reactions, and the fibers are coated with carboxymethyl chitosan on the surface to form an antibacterial water-retaining layer.

Benefits of technology

It significantly improves the water retention performance of bamboo joint draw ropes, reduces liquid respiration phenomenon, and enhances antibacterial performance and improves user comfort.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an antibacterial bamboo joint pull rope material for tampons and a preparation method of the antibacterial bamboo joint pull rope material. Modified bentonite is introduced into an acrylic acid-acrylamide polymer, and a layered structure of the bentonite endows the antibacterial bamboo joint pull rope material with certain water absorption and water retention capacities; meanwhile, amino groups on the modified bentonite are chemically combined with carboxyl groups in the acrylic acid-acrylamide polymer, so that the modified bentonite is not easy to lose; according to the preparation method, firstly, water-absorbing fibers are soaked in a carboxymethyl chitosan solution, the surfaces of the water-absorbing fibers are coated with carboxymethyl chitosan, the carboxymethyl chitosan has excellent water-retaining and antibacterial properties, an antibacterial water-retaining layer is formed on the surfaces of the water-absorbing fibers, and then under the action of a cross-linking agent ethylene glycol diglycidyl ether, the antibacterial water-retaining layer is formed on the surfaces of the water-absorbing fibers. Hydroxyl groups and amino groups in the carboxymethyl chitosan and carboxyl groups and amino groups on the water-absorbing fibers are subjected to a cross-linking effect, so that the bonding strength and the cross-linking density between the carboxymethyl chitosan and the water-absorbing fibers are improved, liquid seepage is effectively prevented, and the water retention performance of the fiber material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sanitary products, and in particular to an antibacterial bamboo drawstring material for tampons and a preparation method thereof. Background Art

[0002] Tampons, also known as sanitary plugs, are a cotton cylinder, mainly made of cotton, synthetic fibers or a mixture of these two materials, with diameters ranging from 1 cm to 1.9 cm, and a drawstring at the end. The convenience of tampons meets the new needs of consumers. Compared with sanitary napkins, women can dress, move, work, exercise, relax, and have fun freely when using tampons, without suffering from leakage or worries. They are gradually being accepted by domestic consumers, especially young people. When women have their period, tampons are inserted into the vagina. They have the effect of strongly absorbing menstrual blood. They have attracted much attention because of their small size, comfortable use, and good absorption capacity.

[0003] A bamboo drawstring is usually provided between the absorbent core and the tail drawstring of a tampon, and its function is to further absorb menstrual blood and prevent side leakage. However, most existing bamboo drawstrings focus on their water absorption capacity while ignoring their water retention capacity. If the bamboo drawstring quickly seeps back a large amount of liquid after absorbing the liquid, it will make the human body feel uncomfortable. Therefore, it is equally important to improve the back-permeability of the bamboo drawstring. Summary of the invention

[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide an antibacterial bamboo drawstring material for tampons and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] In a first aspect, the present invention provides a method for preparing an antibacterial bamboo drawstring material for a tampon, comprising the following steps:

[0007] S1. Preparation of modified bentonite

[0008] The bentonite is dispersed in deionized water, and then polyguanidine salt and epichlorohydrin are added thereto, the pH value of the solution is adjusted to 9-12, and the solution is heated and stirred for reaction. After the reaction is completed, the solution is filtered, washed and dried to obtain the modified bentonite.

[0009] In this step, the mass ratio of bentonite, polyguanidine salt and epichlorohydrin is 8-12:3-5:4-6. In some embodiments of the present invention, for example, 8:3:4, 8:5:6, 10:3:4, 10:5:6, 12:3:4, 12:3:6, 12:5:4, 12:5:6 can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0010] Specifically, the polyguanidine salt is selected from polyhexamethylene biguanide hydrochloride or polyhexamethylene biguanide nitrate.

[0011] In this step, the temperature of the heating and stirring reaction is 75-85°C. In some embodiments of the present invention, for example, 75°C, 78°C, 80°C, 82°C, 84°C, and 85°C can be selected; the time of the heating and stirring reaction is 2-4h, for example, 2h, 2.5h, 3h, 3.5h, and 4h can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0012] In this step, polyguanidine salt is grafted onto bentonite through the action of cross-linking agent epichlorohydrin, thereby improving the antibacterial property of bentonite. At the same time, hydrophilic amino groups are introduced on the surface of bentonite, thereby improving the water absorption property of bentonite and also improving the dispersion property of bentonite in the subsequent system.

[0013] S2. Preparation of spinning solution

[0014] Acrylic acid and acrylamide are added to an ethanol aqueous solution, the pH of the system is adjusted to 5-6, modified bentonite, citronellol and sodium carboxymethyl cellulose are added under nitrogen protection, a crosslinking agent and an initiator are added after uniform dispersion, nitrogen is stopped, heating is performed for reaction, and after the reaction is completed, a viscous liquid is obtained, the viscous liquid is diluted with water to a concentration of 1.5-3wt%, and the pH of the system is maintained at 5-6 to obtain a spinning solution.

[0015] In this step, the mass ratio of acrylic acid, acrylamide, ethanol aqueous solution, modified bentonite, citronellol, sodium carboxymethyl cellulose, crosslinking agent and initiator is 80-90:5-10:200-250:4-8:3-6:2-3:1-2:0.5-1.

[0016] Specifically, the mass fraction of the ethanol aqueous solution is 20-30%, for example, 20%, 22%, 24%, 25%, 28%, 30% can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0017] Specifically, the cross-linking agent is selected from N,N'-methylenebisacrylamide.

[0018] Specifically, the initiator is selected from persulfates, for example, sodium persulfate, potassium persulfate or ammonium persulfate.

[0019] In this step, the temperature of the heating reaction is 60-70°C. In some embodiments of the present invention, for example, 60°C, 62°C, 64°C, 65°C, 66°C, 68°C, 69°C, and 70°C can be selected; the time of the heating reaction is 3-5h, for example, 3h, 3.5h, 4h, 4.5h, and 5h can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] In this step, the solution used to adjust the pH of the system is a sodium hydroxide solution.

[0021] In the present invention, the acrylic acid-acrylamide polymer has extremely strong water absorption, but poor water retention. The present invention introduces modified bentonite into the acrylic acid-acrylamide polymer, and the layered structure of the bentonite gives it a certain water retention capacity. At the same time, the amino groups on the modified bentonite are chemically combined with the carboxyl groups in the acrylic acid-acrylamide polymer, thereby improving the bonding degree between the modified bentonite and the acrylic acid-acrylamide polymer, making it difficult to lose. Citronellol is a natural high molecular compound, has good antibacterial properties, and has high safety. The present invention grafts citronellol into the acrylic acid-acrylamide polymer through the addition of double bonds, and the citronellol and the modified bentonite work together to improve the antibacterial property of the fiber.

[0022] S3. Preparation of water-absorbent fibers

[0023] The spinning solution is added into the syringe, and the spinning solution is ejected from the spinneret to form a thin stream, which is then coagulated in a coagulation bath to form a water-absorbent fiber.

[0024] In this step, the spinning solution is ejected from the spinneret at a speed of 4-6 mL / min.

[0025] In this step, the coagulation bath is a 75-85 wt % ethanol aqueous solution.

[0026] S4. Preparation of composite fibers

[0027] The absorbent fiber is immersed in a carboxymethyl chitosan solution, taken out and dried, then immersed in an ethylene glycol diglycidyl ether solution, taken out and subjected to a heat curing cross-linking reaction to obtain a composite fiber.

[0028] In this step, the mass ratio of the water-absorbing fiber, the carboxymethyl chitosan solution and the ethylene glycol diglycidyl ether solution is 1:15-20:15-20.

[0029] Specifically, the mass fraction of the carboxymethyl chitosan solution is 5-10%, for example, 5%, 6%, 7%, 8%, 9%, 10% can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Specifically, the mass fraction of the ethylene glycol diglycidyl ether solution is 3-6%, for example, 3%, 4%, 5%, 6% can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] In this step, the temperature of the thermal curing cross-linking reaction is 80-90°C, for example, 80°C, 82°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, and 90°C can be selected; the time of the thermal curing cross-linking reaction is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, and 3h can be selected; but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] In the present invention, the absorbent fiber is firstly immersed in a carboxymethyl chitosan solution, and the surface of the absorbent fiber is coated with carboxymethyl chitosan, which has excellent water-retaining and antibacterial properties, and an antibacterial water-retaining layer is formed on the surface of the absorbent fiber. Subsequently, under the action of the cross-linking agent ethylene glycol diglycidyl ether, the hydroxyl group and the amino group in the carboxymethyl chitosan are cross-linked with the carboxyl group and the amino group on the absorbent fiber, thereby improving the bonding strength and the cross-linking density between the carboxymethyl chitosan and the absorbent fiber, effectively preventing liquid seepage, and further improving the water-retaining property of the fiber material.

[0033] S5. Preparation of antibacterial bamboo rope materials

[0034] The composite fiber is spun and twisted to obtain the antibacterial bamboo drawstring material.

[0035] In this step, the composite fiber is spun and twisted using existing technology, and the twisting degree can be selected according to actual needs, which is not limited here.

[0036] In a second aspect, the present invention also provides an antibacterial bamboo drawstring material for tampons prepared by the above preparation method.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention introduces modified bentonite into acrylic acid-acrylamide polymer. The layered structure of bentonite gives it a certain water absorption and water retention capacity. At the same time, the amino groups on the modified bentonite are chemically combined with the carboxyl groups in the acrylic acid-acrylamide polymer, thereby improving the bonding degree between the modified bentonite and the acrylic acid-acrylamide polymer, making it difficult to lose. Citronellol is a natural polymer compound with good antibacterial properties and high safety. The present invention grafts citronellol into the acrylic acid-acrylamide polymer through the addition of double bonds. The citronellol and modified bentonite work together to improve the antibacterial properties of the fiber.

[0039] (2) The present invention first immerses the absorbent fiber in a carboxymethyl chitosan solution, and then coats the surface of the absorbent fiber with carboxymethyl chitosan, which has excellent water-retaining and antibacterial properties, to form an antibacterial water-retaining layer on the surface of the absorbent fiber. Subsequently, under the action of the cross-linking agent ethylene glycol diglycidyl ether, the hydroxyl groups and amino groups in the carboxymethyl chitosan are cross-linked with the carboxyl groups and amino groups on the absorbent fiber, thereby improving the bonding strength and cross-linking density between the carboxymethyl chitosan and the absorbent fiber, effectively preventing liquid seepage, and further improving the water-retaining properties of the fiber material. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0041] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0042] The bentonite used in the present invention is sodium-based bentonite with a mesh size of 1250 meshes.

[0043] Example 1

[0044] A method for preparing an antibacterial bamboo drawstring material for a tampon comprises the following steps:

[0045] S1, 8g of bentonite was dispersed in 100g of deionized water, and then 3g of polyhexamethylene biguanide hydrochloride and 4g of epichlorohydrin were added thereto, the pH of the solution was adjusted to 10, and the mixture was heated and stirred at 75°C for 4h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified bentonite;

[0046] S2, adding 80g acrylic acid and 5g acrylamide to 200g, 20wt% ethanol aqueous solution, adjusting the pH of the system to 5, adding 4g modified bentonite, 3g citronellol and 2g sodium carboxymethyl cellulose under nitrogen protection, adding 1g cross-linking agent N,N'-methylenebisacrylamide and 0.5g initiator ammonium persulfate after uniform dispersion, stopping the nitrogen flow, heating the reaction at 60°C for 5h, after the reaction is completed, a viscous liquid is obtained, and the viscous liquid is diluted with water to a concentration of 2wt%, while maintaining the pH of the system at 5, to obtain a spinning solution;

[0047] S3, adding the spinning solution into the syringe, the spinning solution is ejected from the spinneret to form a thin stream, the spinning solution is ejected from the spinneret at a speed of 5 mL / min, and then coagulated in 80 wt % ethanol aqueous solution to form a water-absorbent fiber;

[0048] S4, immersing 1 kg of the absorbent fiber in 15 kg of a 5 wt% carboxymethyl chitosan solution for 2 h, taking it out and drying it at 60° C., then immersing it in 15 kg of a 3 wt% ethylene glycol diglycidyl ether solution for 2 h, taking it out and heat curing it at 80° C. for a cross-linking reaction for 3 h to obtain a composite fiber;

[0049] S5. Spinning and twisting the composite fiber to obtain an antibacterial bamboo drawstring material.

[0050] Example 2

[0051] A method for preparing an antibacterial bamboo drawstring material for a tampon comprises the following steps:

[0052] S1, dispersing 12g of bentonite in 100g of deionized water, then adding 5g of polyhexamethylene biguanide hydrochloride and 6g of epichlorohydrin, adjusting the pH of the solution to 10, heating and stirring at 85°C for 2h, after the reaction is completed, filtering, washing and drying to obtain modified bentonite;

[0053] S2, adding 90g acrylic acid and 10g acrylamide to 250g, 20wt% ethanol aqueous solution, adjusting the pH of the system to 5, adding 8g modified bentonite, 6g citronellol and 3g sodium carboxymethyl cellulose under nitrogen protection, adding 2g cross-linking agent N,N'-methylenebisacrylamide and 1g initiator ammonium persulfate after uniform dispersion, stopping the nitrogen flow, heating the reaction at 70°C for 3h, after the reaction is completed, a viscous liquid is obtained, and the viscous liquid is diluted with water to a concentration of 1.5wt%, while maintaining the pH of the system at 5 to obtain a spinning solution;

[0054] S3, adding the spinning solution into the syringe, the spinning solution is ejected from the spinneret to form a thin stream, the spinning solution is ejected from the spinneret at a speed of 5 mL / min, and then coagulated in 80 wt % ethanol aqueous solution to form a water-absorbent fiber;

[0055] S4, immersing 1 kg of the absorbent fiber in 15 kg of a 10 wt% carboxymethyl chitosan solution for 2 h, taking it out and drying it at 60° C., then immersing it in 15 kg of a 5 wt% ethylene glycol diglycidyl ether solution for 2 h, taking it out and heat curing it at 90° C. for a cross-linking reaction for 1 h to obtain a composite fiber;

[0056] S5. Spinning and twisting the composite fiber to obtain an antibacterial bamboo drawstring material.

[0057] Example 3

[0058] A method for preparing an antibacterial bamboo drawstring material for a tampon comprises the following steps:

[0059] S1, dispersing 10g of bentonite in 100g of deionized water, then adding 4g of polyhexamethylene biguanide hydrochloride and 5g of epichlorohydrin, adjusting the pH of the solution to 10, heating and stirring at 80°C for 3h, after the reaction is completed, filtering, washing and drying to obtain modified bentonite;

[0060] S2, adding 85g of acrylic acid and 8g of acrylamide to 250g of 20wt% ethanol aqueous solution, adjusting the pH of the system to 5, adding 5g of modified bentonite, 4g of citronellol and 2g of sodium carboxymethyl cellulose under nitrogen protection, adding 1.5g of cross-linking agent N,N'-methylenebisacrylamide and 0.8g of initiator ammonium persulfate after uniform dispersion, stopping the introduction of nitrogen, heating the reaction at 65°C for 4h, and after the reaction is completed, a viscous liquid is obtained, and the viscous liquid is diluted with water to a concentration of 3wt%, while maintaining the pH of the system at 5 to obtain a spinning solution;

[0061] S3, adding the spinning solution into the syringe, the spinning solution is ejected from the spinneret to form a thin stream, the spinning solution is ejected from the spinneret at a speed of 5 mL / min, and then coagulated in 80 wt % ethanol aqueous solution to form a water-absorbent fiber;

[0062] S4, immersing 1 kg of the absorbent fiber in 20 kg of a 5 wt% carboxymethyl chitosan solution for 2 hours, taking it out and drying it at 60°C, then immersing it in 15 kg of a 6 wt% ethylene glycol diglycidyl ether solution for 2 hours, taking it out and heat curing it at 85°C for 2 hours to obtain a composite fiber;

[0063] S5. Spinning and twisting the composite fiber to obtain an antibacterial bamboo drawstring material.

[0064] Comparative Example 1

[0065] A method for preparing an antibacterial bamboo drawstring material for a tampon comprises the following steps:

[0066] S1, adding 80g acrylic acid and 5g acrylamide to 200g, 20wt% ethanol aqueous solution, adjusting the pH of the system to 5, adding 4g bentonite, 3g citronellol and 2g sodium carboxymethyl cellulose under nitrogen protection, adding 1g cross-linking agent N,N'-methylenebisacrylamide and 0.5g initiator ammonium persulfate after uniform dispersion, stopping the nitrogen flow, heating the reaction at 60°C for 5h, after the reaction is completed, a viscous liquid is obtained, and the viscous liquid is diluted with water to a concentration of 2wt%, while maintaining the pH of the system at 5, to obtain a spinning solution;

[0067] S2, adding the spinning solution into the syringe, the spinning solution is ejected from the spinneret to form a thin stream, the spinning solution is ejected from the spinneret at a speed of 5 mL / min, and then coagulated in 80 wt % ethanol aqueous solution to form a water-absorbent fiber;

[0068] S3, immersing 1 kg of the absorbent fiber in 15 kg of a 5 wt% carboxymethyl chitosan solution for 2 h, taking it out and drying it at 60° C., then immersing it in 15 kg of a 3 wt% ethylene glycol diglycidyl ether solution for 2 h, taking it out and heat curing it at 80° C. for a cross-linking reaction for 3 h to obtain a composite fiber;

[0069] S4, spinning and twisting the composite fiber to obtain the antibacterial bamboo drawstring material.

[0070] Compared with Example 1, Comparative Example 1 did not perform any modification treatment on the bentonite.

[0071] Comparative Example 2

[0072] A method for preparing an antibacterial bamboo drawstring material for a tampon comprises the following steps:

[0073] S1, 8g of bentonite was dispersed in 100g of deionized water, and then 3g of polyhexamethylene biguanide hydrochloride and 4g of epichlorohydrin were added thereto, the pH of the solution was adjusted to 10, and the mixture was heated and stirred at 75°C for 4h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified bentonite;

[0074] S2, adding 80g acrylic acid and 5g acrylamide to 200g, 20wt% ethanol aqueous solution, adjusting the pH of the system to 5, adding 4g modified bentonite, 3g citronellol and 2g sodium carboxymethyl cellulose under nitrogen protection, adding 1g cross-linking agent N,N'-methylenebisacrylamide and 0.5g initiator ammonium persulfate after uniform dispersion, stopping the nitrogen flow, heating the reaction at 60°C for 5h, after the reaction is completed, a viscous liquid is obtained, and the viscous liquid is diluted with water to a concentration of 2wt%, while maintaining the pH of the system at 5, to obtain a spinning solution;

[0075] S3, adding the spinning solution into the syringe, the spinning solution is ejected from the spinneret to form a thin stream, the spinning solution is ejected from the spinneret at a speed of 5 mL / min, and then coagulated in 80 wt % ethanol aqueous solution to form a water-absorbent fiber;

[0076] S4, spinning and twisting the water-absorbing fiber to obtain the antibacterial bamboo drawstring material.

[0077] Compared with Example 1, in Comparative Example 2, carboxymethyl chitosan is not coated on the surface of the water-absorbent fiber.

[0078] Comparative Example 3

[0079] A method for preparing an antibacterial bamboo drawstring material for a tampon comprises the following steps:

[0080] S1, 8g of bentonite was dispersed in 100g of deionized water, and then 3g of polyhexamethylene biguanide hydrochloride and 4g of epichlorohydrin were added thereto, the pH of the solution was adjusted to 10, and the mixture was heated and stirred at 75°C for 4h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified bentonite;

[0081] S2, adding 80g acrylic acid and 5g acrylamide to 200g, 20wt% ethanol aqueous solution, adjusting the pH of the system to 5, adding 4g modified bentonite, 3g citronellol and 2g sodium carboxymethyl cellulose under nitrogen protection, adding 1g cross-linking agent N,N'-methylenebisacrylamide and 0.5g initiator ammonium persulfate after uniform dispersion, stopping the nitrogen flow, heating the reaction at 60°C for 5h, after the reaction is completed, a viscous liquid is obtained, and the viscous liquid is diluted with water to a concentration of 2wt%, while maintaining the pH of the system at 5, to obtain a spinning solution;

[0082] S3, adding the spinning solution into the syringe, the spinning solution is ejected from the spinneret to form a thin stream, the spinning solution is ejected from the spinneret at a speed of 5 mL / min, and then coagulated in 80 wt % ethanol aqueous solution to form a water-absorbent fiber;

[0083] S4, immersing 1 kg of the absorbent fiber in 15 kg of a 5 wt% carboxymethyl chitosan solution for 2 h, taking it out and drying it at 60° C. to obtain a composite fiber;

[0084] S5. Spinning and twisting the composite fiber to obtain an antibacterial bamboo drawstring material.

[0085] Compared with Example 1, in Comparative Example 3, after the water-absorbent fiber was coated with carboxymethyl chitosan, no cross-linking treatment was performed using ethylene glycol diglycidyl ether.

[0086] The composite fibers obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, as follows:

[0087] Water absorption and water retention test: Weigh the composite fibers obtained in Examples 1-3 and Comparative Examples 1-3, record the mass as m1, then add them to 100 mL of distilled water, soak them at 25°C for 3 hours, take them out and place them on a metal mesh with a pore size of 3 mm, weigh them until there is no water droplet, and record their weight m2 to calculate the water absorption; then move the fiber sample after water absorption into a dryer at 25°C and 40% RH, take them out and weigh them after drying for 24 hours, record their weight m3, and calculate the water retention;

[0088] Water absorption rate = (m2-m1) / m1×100%

[0089] Water retention rate = (m3-m1) / m1×100%

[0090] Each group was tested 5 times and the results were averaged. The test results are shown in the following table:

[0091] Water absorption (%) Water retention rate (%) Example 1 582 540 Example 2 647 612 Example 3 608 586 Comparative Example 1 535 501 Comparative Example 2 420 343 Comparative Example 3 594 482

[0092] The composite fibers obtained in Examples 1-3 and Comparative Examples 1-3 were spun, twisted, and woven into fabrics, the weight of which was 210±5 g / m 2 , followed by antibacterial performance tests, as follows:

[0093] First, prepare 2×10 5 cfu / ml bacterial suspension (Staphylococcus aureus ATCC 6538, Escherichia coli ATCC8099), then place the fabrics to be tested flat on sterile plates, take 0.4mL of bacterial suspension and drop it in the center of the fabrics, spread it evenly, and cover it with a film; place it at 35℃ and relative humidity 90% for 24h, then wash it, dilute it (PBS), count it after culture, and calculate the inhibition rate;

[0094] The test results are shown in the following table:

[0095] Escherichia coli inhibition rate (%) Staphylococcus aureus inhibition rate (%) Example 1 99.8 99.6 Example 2 99.9 99.4 Example 3 99.8 99.7 Comparative Example 1 96.4 93.9 Comparative Example 2 94.3 92.5 Comparative Example 3 99.7 99.8

[0096] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A method for preparing an antibacterial bamboo drawstring material for tampons, characterized in that: The steps include: S1, dispersing bentonite in deionized water, then adding polyguanidine salt and epichlorohydrin thereto, adjusting the pH of the solution to 9-12, heating and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain modified bentonite; S2, adding acrylic acid and acrylamide to an ethanol aqueous solution, adjusting the pH of the system to 5-6, adding modified bentonite, citronellol and sodium carboxymethyl cellulose under nitrogen protection, adding a crosslinking agent and an initiator after uniform dispersion, stopping the introduction of nitrogen, heating the reaction, and after the reaction is completed, obtaining a viscous liquid, diluting the viscous liquid with water to a concentration of 1.5-3wt%, while maintaining the pH of the system at 5-6, to obtain a spinning solution; S3, adding the spinning solution into the syringe, the spinning solution is ejected from the spinneret to form a thin stream, and then coagulated in a coagulation bath to form a water-absorbing fiber; S4, immersing the absorbent fiber in a carboxymethyl chitosan solution, taking it out and drying it, then immersing it in an ethylene glycol diglycidyl ether solution, taking it out and performing a heat curing cross-linking reaction to obtain a composite fiber; S5. Spinning and twisting the composite fiber to obtain an antibacterial bamboo drawstring material.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of bentonite, polyguanidine salt and epichlorohydrin is 8-12:3-5:4-6, wherein the polyguanidine salt is selected from polyhexamethylene biguanide hydrochloride or polyhexamethylene biguanide nitrate.

3. The preparation method according to claim 1, characterized in that: In step S1, the temperature of the heating and stirring reaction is 75-85° C., and the time of the heating and stirring reaction is 2-4 h.

4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of acrylic acid, acrylamide, ethanol aqueous solution, modified bentonite, citronellol, sodium carboxymethyl cellulose, crosslinking agent and initiator is 80-90:5-10:200-250:4-8:3-6:2-3:1-2:0.5-1, and the mass fraction of the ethanol aqueous solution is 20-30%.

5. The preparation method according to claim 1, characterized in that: In step S2, the cross-linking agent is selected from N,N'-methylenebisacrylamide, and the initiator is selected from persulfate.

6. The preparation method according to claim 1, characterized in that: In step S2, the heating reaction temperature is 60-70°C, and the heating reaction time is 3-5h.

7. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the water-absorbing fiber, the carboxymethyl chitosan solution and the ethylene glycol diglycidyl ether solution is 1:15-20:15-20.

8. The preparation method according to claim 1, characterized in that: In step S4, the mass fraction of the carboxymethyl chitosan solution is 5-10%, and the mass fraction of the ethylene glycol diglycidyl ether solution is 3-6%.

9. The preparation method according to claim 1, characterized in that: In step S4, the temperature of the heat curing cross-linking reaction is 80-90° C., and the time of the heat curing cross-linking reaction is 1-3 hours.

10. The antibacterial bamboo drawstring material for tampons prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Long-acting antibacterial polypropylene non-woven fabric and preparation method thereof

    CN121719018A

  • Reverse osmosis high-absorption type sanitary nursing pad and preparation process thereof

    CN121943568A